2015
DOI: 10.1371/journal.pone.0122665
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Echocardiography in Adult Zebrafish Reveals Delayed Recovery of Heart Function after Myocardial Cryoinjury

Abstract: Translucent zebrafish larvae represent an established model to analyze genetics of cardiac development and human cardiac disease. More recently adult zebrafish are utilized to evaluate mechanisms of cardiac regeneration and by benefiting from recent genome editing technologies, including TALEN and CRISPR, adult zebrafish are emerging as a valuable in vivo model to evaluate novel disease genes and specifically validate disease causing mutations and their underlying pathomechanisms. However, methods to sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 57 publications
6
76
0
Order By: Relevance
“…Moreover, cardiac performance in adult zebrafish can be detected by new noninvasive methods. It can be assessed by advancing conventional echocardiography with speckle-tracking analyses and changes in cardiac performance, and enables highly sensitive assessment of regional myocardial motion and deformation in high spatio-temporal resolution [34] . Then in vivo studies represent an essential step in drug development and toxicity study, and the zebrafish cardiotoxicity test has been reported very reliable, describing the potential toxicity of drugs to the human cardiovascular system [35] .…”
Section: Zebrafish As Cardiotoxicological Toolmentioning
confidence: 99%
“…Moreover, cardiac performance in adult zebrafish can be detected by new noninvasive methods. It can be assessed by advancing conventional echocardiography with speckle-tracking analyses and changes in cardiac performance, and enables highly sensitive assessment of regional myocardial motion and deformation in high spatio-temporal resolution [34] . Then in vivo studies represent an essential step in drug development and toxicity study, and the zebrafish cardiotoxicity test has been reported very reliable, describing the potential toxicity of drugs to the human cardiovascular system [35] .…”
Section: Zebrafish As Cardiotoxicological Toolmentioning
confidence: 99%
“…The regenerated heart, following cryoinjury, exhibits a normal electrocardiogram 30 days after injury, suggesting that new cardiomyocytes are functionally integrated into the preexisting myocardium (Chablais and Jazwinska, 2012). A detailed examination, however, indicated that cryoinjury induces long-term alterations in myocardial organization (Gonzalez-Rosa et al, 2014), and functional recovery extends up to 6 months (Hein et al, 2015). …”
Section: Zebrafish Model For Heart Regeneration Researchmentioning
confidence: 99%
“…To date, many studies have identified various signals that regulate cardiomyocyte proliferation in response to injury in adult zebrafish. These include retinoic acid (RA) signaling (Kikuchi et al, 2011b), Hif1 signaling (Jopling et al, 2012), Jak1-STAT3 signaling (Fang et al, 2013), hedgehog signaling, transforming growth factor ß (TGFß) signaling, insulin-like growth factor (IGF) signaling (Chablais and Jazwinska, 2012;Choi et al, 2013), bone morphogenetic protein (BMP) signaling (Wu et al, 2016), redox signaling (Hein et al, 2015), NF-kappaB signaling , and Neureglin1 (Nrg1)-ErbB signaling .…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…14 Overall, despite the aforementioned limitations, the use of a microprobe for intracoronary imaging in humans can easily be used to evaluate ventricle size and function in adult zebrafish and could be an alternative to other more expensive echocardiography devices. 11,14,18 Although echocardiography has been used to assess the heart of zebrafish, we are the first to report the use of coronary ultrasound probes, designed for humans, in the adult zebrafish. The major advantage of echocardiography probes designed for small animals (usually mice) is image quality.…”
Section: Discussionmentioning
confidence: 99%